Previous tumour as a prognostic factor in stage I non-small cell lung cancer. Issue 5 (31st January 2006) - López-Encuentra, Angel; Gómez de la Cámara, Agustín; Rami-Porta, Ramón; Duque-Medina, José Luis; de Nicolás, José Luis Martín; Sayas, Javier
Abstract : Objective: To evaluate the effect of comorbidity as an independent prognostic factor in lung cancer. Method: Data on 2991 consecutive cases of lung cancer were collected prospectively from 19 Spanish hospitals between 1993 and 1997 by the Bronchogenic Carcinoma Cooperative Group of the Spanish Society of Pneumology and Thoracic Surgery (GCCB-S). To evaluate the effect of comorbidity on survival, 1121 patients with non-small cell lung cancer (NSCLC) in pathological stage I who underwent complete resection were selected, excluding operative mortality. The presence of specific comorbidities at the time of thoracotomy was registered prospectively. Results: Cox regression analysis showed that tumour size (0–2, 2–4, 4–7, >7 cm) (HR 1.45 95% CI 1.08 to 1.95), 1.86 (95% CI 1.38 to 2.51), 2.84 (95% CI 1.98 to 4.08)), the presence of a previous tumour (HR 1.45 (95% CI 1.17 to 1.79)) and age (HR 1.02 (95% CI 1.01 to 1.03)) had a significant prognostic association with survival. This study excluded the presence of visceral pleural involvement or other comorbidities as independent variables. Conclusion: The presence of a previous tumour is an independent prognostic factor in pathological stage I NSCLC with complete resection, increasing the probability of death by 1.5 times at 5 years. It is independent of other comorbidities, TNM classification and age.